The Dialectics of Student Well-being in the Free Nutritious Meals Program Policy: The Intersection of Economics and Psychology - Rohim, Ubaidillah; Fauziah, Arinal Haq (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
Student well-being is a crucial aspect of education as it influences physical and psychological health, as well as academic achievement. This study analyses the impact of the Free Nutritious Meals Programme (MBG) on student well-being from economic and psychological perspectives. A phenomenological qualitative approach was used to explore the experiences of children and parents from lower-middle-income families through in-depth interviews and observation. The results indicate that the MBG has not yet had a significant economic impact on reducing household expenditure burdens, as there has been no change in consumption patterns or family financial allocation. From a psychological perspective, students’ low acceptance of the food has led to discomfort, rejection, and a tendency towards negative self-perception. These findings underscore that student well-being is dialectical, necessitating a more comprehensive policy evaluation to ensure alignment with students’ needs and experiences.